Amor Fati as Practice: How to Love Fate. Issue 2 (June 2016) - Elgat, Guy
ABSTRACT: On the basis of an interpretation of key passages in The Gay Science, this paper examines Nietzsche's idea of amor fati —love of fate. Nietzsche's idea of amor fati involves the wish to be able to learn how to see things as beautiful. This gives the impression that amor, love, is supposed to play some role in the beautification of fate. But Nietzsche also explains amor fati in relation to his desire to be a devoted "Yes‐sayer." This pulls the interpretation of amor in a different direction; for now it seems as if the love Nietzsche wants to cultivate is supposed to be expressed in a positive, affirmative attitude toward one's fate. How to think this duality under the single idea of amor fati ? I develop a novel reading of amor fati as a form of practice, as something that we can do, and explain in its light how the two moments of love are to be brought together. The relation of amor fati to the "Eternal Recurrence of the Same" is also addressed: mastering the practice of amor fati can enable one to pass successfully the test of the Eternal Recurrence of the Same.